SPE Annual Technical Conference and Exhibition 2006
DOI: 10.2118/102970-ms
|View full text |Cite
|
Sign up to set email alerts
|

Choked Flow in HVO Recovery: Injection and Production in Horizontal Wells

Abstract: The problem of multiphase flows in chokes presents an interesting problem for steam injection and hydrocarbon production. In both cases it is important to evaluate the maximum possible mass fluxes through a perforation. Several models are used in the oil industry for this purpose, e.g., Ashford (1974) [1], Sachdeva et al. (1984) [2], and Perkins (1993) [3]. This paper explains physical principles behind these theories, and outlines their range of applicability. The task of the study is to choose a model that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A literature search for papers pertaining to multiphase flow through wellhead chokes revealed that multiple researchers have developed empirically and theoretically derived correlations for the prediction of multiphase flow through wellhead chokes. The empirical correlation that appeared to be the most directly applicable was developed by Gilbert (1954) for critical multiphase flow through a wellhead choke, which takes the following form (Poettmann and Beck 1963;Omana et al 1969;Fortunati 1972;Ashford 1974;Ashford and Pierce 1975;Sachdeva et al 1986;Ajienka and Ikoku 1987;Al-Attar and Abdul-Majeed 1988;Surbey et al 1988Surbey et al , 1989Ghassan and Maha 1991;Osman and Dhokla 1992;Perkins 1993;Ajienka et al 1994;Al-Towailib and Al-Marhoun 1994;Elgibaly and Nashawi 1998;Guo et al 2002Guo et al , 2007Burstev et al 2006;Schuller et al 2003Schuller et al , 2006Alsafran and Kelkar 2007;Ghareeb and Shedid 2007;Al-Attar 2008, 2010Nasriani and Kalantariasl 2011):…”
Section: Methodology Comparisonmentioning
confidence: 99%
“…A literature search for papers pertaining to multiphase flow through wellhead chokes revealed that multiple researchers have developed empirically and theoretically derived correlations for the prediction of multiphase flow through wellhead chokes. The empirical correlation that appeared to be the most directly applicable was developed by Gilbert (1954) for critical multiphase flow through a wellhead choke, which takes the following form (Poettmann and Beck 1963;Omana et al 1969;Fortunati 1972;Ashford 1974;Ashford and Pierce 1975;Sachdeva et al 1986;Ajienka and Ikoku 1987;Al-Attar and Abdul-Majeed 1988;Surbey et al 1988Surbey et al , 1989Ghassan and Maha 1991;Osman and Dhokla 1992;Perkins 1993;Ajienka et al 1994;Al-Towailib and Al-Marhoun 1994;Elgibaly and Nashawi 1998;Guo et al 2002Guo et al , 2007Burstev et al 2006;Schuller et al 2003Schuller et al , 2006Alsafran and Kelkar 2007;Ghareeb and Shedid 2007;Al-Attar 2008, 2010Nasriani and Kalantariasl 2011):…”
Section: Methodology Comparisonmentioning
confidence: 99%